(untitled) (Mustansiria Dental Journal, 2019)
Objectives: The aim of the present study was to compare the effectiveness of Endovac, Vibringe and needle with different irrigation solutions on removal of smear layer and apical extrusion of irrigating solution. Methods: Seventy-two sound human premolar teeth were used and divided into three experimental groups (n=24) according to the type of irrigation technique used: Ingroup 1 irrigation was performed with Vibringe. In-group 2 irrigation was performed with a 30-gauge side-vented irrigation needle. In-group 3 irrigation was performed with Endovac. Instrumentation was performed by using the ProTaper files. Each main group divided into three sub-groups (n=8) according to irrigation solution used: In sub-group 1 Irrigation was performed with 5.25% Sodium hypochlorite (NaOCL). In sub-group 2 Irrigation was performed with 17% Ethylene Diamin Tetra Acidic Acid (EDTA). In sub-group 3 Irrigation was performed with 5.25% NaOCL and 17 % EDTA. The amount of extruded irrigating solution was then measured by subtracting the weight before final irrigation from the weight after final irrigation using the electronic balance. The cleanliness of smear layer removal was evaluated using scanning electron microscopy. Results: The results showed that the group that resulted in more irrigation extrusion was as follow from highest to lowest: side-vented >Vibringe> Endovac. The difference among all groups was significant. As for cleaning results, smear layer collection in both EndoVac and Vibringe groups were less than side-vented group and these differences were significant. When the three irrigating solutions compared the differences among all the groups were significant and combination of (5.25% NaOCL and 17 % EDTA) resulted in more smear layer removal. Conclusion: In conclusion, the EndoVac irrigation system extruded significantly less irrigant solution than both the Vibringe and needle irrigation systems. Smear layer collection was least in the apical third regarding the EndoVac irrigation system and resulted in more Smear layer removal. And combination of NaOCL and EDTA group was more effective on smear layer removal than other two groups.